IMPLEMENTASI EVALUASI PEMBELAJARAN PAI PADA KURIKULUM MERDEKA BELAJAR - Hilmiyati, Fitri; Pratiwi, Herlina; Fajriah, Nurul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The problems that occur at driving schools in implementing the Kurikulum Merdeka Belajar (KMB) are identified as follows: 1. Limited human resources at driving schools in implementing the KMB. 2. Limited facilities and infrastructure for implementing the KMB. 3. Limited support from parents in implementing the KMB. 4. Awareness has not yet been raised among teachers to implement the KMB. 5. Limited encouragement from the school to improve learning through the KMB. The implementation of KMB, which aims to instill character education in students, has an impact on the implementation of learning carried out by Islamic Religious Education (PAI) teachers. In the context of the curriculum, learning evaluation has the function of finding out whether the goals that have been set have been achieved or not, this becomes feedback for teachers in improving the learning carried out. It is necessary to carry out further research on the implementation of learning evaluations carried out by PAI teachers at KMB to strengthen and increase the effectiveness of its implementation in developing students’ life skills, creativity and character.